COMMUNITY LOSS OF RESIDENTIAL VALUE FROM WATER AND NOISE POLLUTION - Iman, Abdul Hamid Mar; Gan, Christopher (Journal of Techno-Social, 2013)
The impact of environmental disamenity on residential value had continued to receive attention in the property market. This study estimates community loss of residential value resulting from water and noise pollutions in the local neighbourhoods. The study areas comprised residential neighbourhoods nearby sources of such pollutions. Upon integration of the digital cadastre and house transaction data, digital maps were used to identify parcels of residential properties that were presumably affected by such pollutions in the study areas. Using the overlay and buffering functions, two proxy environmental variables were included in the regression models to capture pollution effects on residential values. The analysis disclosed that houses located closer to water and noise pollution were sold at lower prices compared to those located farther away from it. The total amount of community loss of â€œpollution-imposedâ€ residential value in seven selected neighbourhoods was in excess of RM 57 million. The evidence shows that house buyers regard environmental quality as an important factor in real estate transaction. In particular, environmental disamenity resulting from water and noise pollution could have been negatively capitalised into residential values.